Application of Computer Network Multimedia Technology in Vocal Music Teaching Mode - Liu Xizhi (MATEC Web of Conferences, 2022)
Nowadays, with the continuous development of the times, multimedia technology(MT) is rapidly infiltrating people's lives, and people are paying more and more attention to multimedia teaching, which has been well applied in vocal music(VM) teaching. Since VM is a highly practical and relatively abstract subject, it is necessary to organically combine theory with practice. In addition, nowadays people have higher and higher requirements for music aesthetics, and the enrollment scale of VM majors is increasing, making traditional teaching methods no longer able to meet the needs of vocal talents. Because the network MT can well solve the problems in the traditional classroom and make up for the shortcomings, it has played an important role in improving classroom efficiency, improving the quality of teaching and teaching effects. At the same time, the use of modern methods for VM teaching can also provide teachers with more convenience. Therefore, under this background, it is necessary to combine modern education methods with VM teaching mode(VMTM) to realize the transformation of VMTM. This article uses questionnaire survey method and data analysis method to make use of the advantages of computer network MT to make VM teaching simpler and more intuitive, so as to achieve better VM teaching effects. According to the survey results, most interviewees believe that the application of computer network MT in the VMTM has certain effects and brings a lot of vitality to the development of the course.